THE EFFECT OF SHARE OWNERSHIP STRUCTURE ON THE RISK OF EXPROPRIATION IN COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Muh. Abdi Imam; Gagaring Pagalung; Grace T. Pontoh (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2016)
Studies of the risks of expropriation has been done by researchers, there is no consistency in the results of these studies because of differences in the characteristics of companies in each country. The research aimed at examining empirically the effect of the share ownership structure towards the expropriation risk on the companies registered in Indonesia Stock Exchange in the period of 2010-2014. The research was conducted by downloading the financial report summary of the nonfinancial companies. Samples selected were as many as 61 non-financial companies registered in Indonesia Stock Exchange in the period of 2010-2014. The data were analysed by the quantitative approach, namely by the multiple linear regression analysis using SPSS 21. The result of the simultaneous test indicates that the share ownership structure has the effect on the expropriation risk. Partially, the institusional and public ownership have the negative effect on the expropriation risk, and the individual ownership has the positive effect on the expropriation risk. The expropriation risk carried out by the controlling share holders on the non-controlling share holders is smaller than the share ownership by the institutional and public ownerships because it can act as the monitoring party on the management performance as the company’s managementKeywords: institutional ownership, public ownership, individual ownership, and expropriation risk.